Sharing data for future research-engaging participants' views about data governance beyond the original project: a DIRECT study - Shah, N; Coathup, V; Teare, H; Forgie, I; Giordano, G; Hansen, T; Groeneveld, L; Hudson, M; Pearson, E; Ruetten, H; Kaye, J (Springer Nature, 2018)
Purpose Biomedical data governance strategies should ensure that data are collected, stored, and used ethically and lawfully. However, research participants’ preferences for how data should be governed is least studied. The Diabetes Research on Patient Stratification (DIRECT) project collected substantial amounts of health and genetic information from patients at risk of, and with type II diabetes. We conducted a survey to understand participants’ future data governance preferences. Results will inform the postproject data governance strategy. Methods A survey was distributed in Denmark, Sweden, The Netherlands, and the United Kingdom. Results In total 855 surveys were returned. Ninety-seven percent were supportive of sharing data postproject, and 90% were happy to share data with universities, and 56% with commercial companies. The top three priorities for data sharing were highly secure database, DIRECT researchers to monitor data used by other researchers, and researchers cannot identify participants. Respondents frequently suggested that a postproject Data Access Committee should involve a DIRECT researcher, diabetes clinician, patient representative, and a DIRECT participant. Conclusion Preferences of how data should be governed, and what data could be shared and with whom varied between countries. Researchers are considered as key custodians of participant data. Engaging participants aids in designing governance to support their choices.